Faktor yang Mempengaruhi Perkembangan Peserta Didik Anak Kelas 1 Sekolah Dasar - Ramadan Lubis; Eed Darul Haq; Rahmat Selian; Nur Azizah; Melysa Indriani; Nuri Afia (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to describe the factors influencing the development of first-grade elementary school students, with a particular focus on physical development as the foundation for other developmental aspects. This research employed a qualitative descriptive approach, with the subject being a first-grade student named Muhammad Dimas Prayuda and the main informant, his mother Mrs. Melinda. Data were collected through in-depth interviews, indirect observation, and documentation conducted on Wednesday, November 5, 2025. The results indicate that the child’s development is influenced by both internal and external factors, including physical condition, parenting style, family environment, and teacher support at school. Dimas demonstrated good physical and social development due to a supportive family environment but still needed assistance in managing emotions and adapting to new learning settings. This study highlights the importance of collaboration between schools and parents in fostering a conducive learning environment that supports children’s holistic development.